Possibilities of Using Laser Radiation in Vitreoretinal Surgery - D. V. Petrachkov; E. N. Korobov (Oftalʹmologiâ)
Currently, laser technologies are widely used in the treatment of diseases of the eye and its accessory apparatus. Basically, they are used in oculoplastic surgery during operations on the accessory apparatus of the eye, in refractive and corneal surgery, laser support for ultrasound cataract surgery, laser treatment of glaucoma, laser coagulation of the retina, thermotherapy of choroidal formations. In the 21st century, Nd: YAG laser treatment of floating opacities in the vitreous body began to be actively popularized with mixed results. In vitreoretinal surgery, which is improving every decade, laser technology remains at the level of the 20th century. In endovitreal surgery, the laser is still used only for endolaser coagulation of the retina, despite the fact that there is a huge potential for using lasers as a “laser scalpel” for removing the vitreous, precision removal of a retinal tear, epiretinal fibrosis, precision retinotomy, and choroidotomy. In this regard, it is necessary to search for the most suitable laser radiation, which will make it possible to carry out thin cuts on the retina and choroid with high accuracy, minimal damage to the surrounding tissues, and a sufficient degree of coagulation to prevent hemorrhages. This laser will allow for surgical interventions in the posterior eye segment with a lower risk of intra- and postoperative complications, as well as better anatomical and functional results. With further development, this new approach to laser ablation may become an alternative to mechanical instruments for surgical dissection and removal of pathological tissue from the surface of the retina.